Prevalence of antimicrobial resistance in bacteria isolated from central nervous system specimens as reported by U.S. hospital laboratories from 2000 to 2002 - Karlowsky James A; Draghi Deborah C; Jones Mark E; Sahm Daniel F; Bradley John S (Annals of Clinical Microbiology and Antimicrobials, 2004)
Abstract Background Bacterial infections of the central nervous system, especially acute infections such as bacterial meningitis require immediate, invariably empiric antibiotic therapy. The widespread emergence of resistance among bacterial species is a cause for concern. Current antibacterial susceptibility data among central nervous system (CNS) pathogens is important to define current prevalence of resistance. Methods Antimicrobial susceptibility of pathogens isolated from CNS specimens was analyzed using The Surveillance Database (TSN®) USA Database which gathers routine antibiotic susceptibility data from >300 US hospital laboratories. A total of 6029 organisms derived from CNS specimen sources during 2000–2002, were isolated and susceptibility tested. Results Staphylococcus aureus (23.7%) and Streptococcus pneumoniae (11.0%) were the most common gram-positive pathogens. Gram-negative species comprised approximately 25% of isolates. The modal patient age was 1 or <1 year for most organisms. Prevalence of MRSA among S. aureus from cerebrospinal fluid (CSF) and brain abscesses were 29.9–32.9%. Penicillin resistance rates were 16.6% for S. pneumoniae, 5.3% for viridans group streptococci, and 0% for S. agalactiae. For CSF isolates, ceftriaxone resistance was S. pneumoniae (3.5%), E. coli (0.6%), Klebsiella pneumoniae (2.8%), Serratia marcescens (5.6%), Enterobacter cloacae (25.0%), Haemophilus influenzae (0%). Listeria monocytogenes and N. meningitidis are not routinely susceptibility tested. Conclusions Resistance is commonly detected, albeit still at relatively low levels for key drugs classes such as third-generation cephalosporins. This data demonstrates the need to consider predominant resistance phenotypes when choosing empiric therapies to treat CNS infections.